1998
DOI: 10.1212/wnl.50.6.1896
|View full text |Cite
|
Sign up to set email alerts
|

Visual activation patterns in patients with optic neuritis

Abstract: We studied the use of functional MRI (fMRI) with visual stimulation in nine patients with unilateral optic neuritis. Eight healthy subjects served as controls. Patients showed reduced activation upon stimulation of the affected eye, on average 33% (range 0 to 156%) of the average monocular activation in the control group. Decreased activation was also seen for the unaffected eye (61% of control values, range 3 to 133%). We conclude that fMRI with visual stimulation is feasible in patients with optic neuritis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
38
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 0 publications
4
38
1
Order By: Relevance
“…Relatively few fMRI studies have assessed the visual system in patients with MS [68,101,125]. A preliminary report demonstrated that recovery from optic neuritis is associated with a change in the cerebral response to photic stimulation [125].…”
Section: ■ Structural Mr Findingsmentioning
confidence: 99%
“…Relatively few fMRI studies have assessed the visual system in patients with MS [68,101,125]. A preliminary report demonstrated that recovery from optic neuritis is associated with a change in the cerebral response to photic stimulation [125].…”
Section: ■ Structural Mr Findingsmentioning
confidence: 99%
“…Most studies have used paradigms for the visual and motor systems and have addressed clinically isolated syndromes, [2][3][4][5][6][7][8][9] relapsing-remitting multiple sclerosis (MS), 10 -15 secondary progressive MS, 16 and primary progressive MS. 17,18 The most persuasive evidence for adaptive cortical plasticity comes from those studies above in which stable patients with preserved clinical function demonstrate altered fMRI activation that also correlates with structural central nervous system damage. This suggests that cortical reorganization after MS injury may have a role in limiting clinical disability.…”
mentioning
confidence: 99%
“…19 -21 We focused on two visual function markers (logarithm of the minimum angle of resolution [logMAR] visual acuity and 30-2 Humphrey visual field mean deviation [HMD] scores) and two optic nerve structural MRI markers (the crosssectional area measured by fat-saturated short echo fast fluid-attenuated inversion recovery sequence and the baseline gadolinium-enhanced lesion length). Our aims were: (1) to investigate the direct relationships between optic nerve structure, visual function, and functional activation and their variation over time; (2) to apply a novel technique that related fMRI to clinical function after accounting for any confounding structural influences, thereby effectively searching for true adaptive cortical reorganization; and (3) to investigate whether the rate of early clinical recovery was related to the corresponding fMRI response.…”
mentioning
confidence: 99%
“…Less activation of visual cortex is seen in patients with both acute and previous ON than in controls, which probably represents reduced neuronal input due to acute pathological changes in the nerve such as oedema, inflammation, and later demyelination and axonal loss [21,27,60,83,85,98,109]. Increases in BOLD signal correlate significantly with both Snellen's visual acuity and contrast sensitivity measurements [60].…”
Section: ■ Functional Mrimentioning
confidence: 99%